فاعلية برنامج مقترح للرفع من مستوى المساندة بين الزوجين للتكفل بطفل في وضعية إعاقة - أنفال نوري; وهيبة بوخزنة (جامعة الوادي - University of Eloued, 2025)
" ملخص الدراسة: سعت هذه الدراسة إلى بناء برنامج إرشادي نفسي يهدف إلى رفع مستوى المساندة بين الزوجين المتكفلين بطفل في وضعية إعاقة، انطلاقًا من ملاحظة ميدانية قامت بها الباحثتان لحالات عديدة واردة إلى عيادة ""إسراء الخير للصحة النفسية والأرطوفونية""، حيث تبين وجود صعوبات نفسية واجتماعية تؤثر سلبًا على العلاقة الزوجية وتحدّ من قدرة الأزواج على التفاهم والتكافل في ظل ضغوط الإعاقة. ومن أجل تشخيص الوضع بدقة، قامت الباحثتان بإجراء دراسة استطلاعية على عينة مكونة من ثلاثين زوجًا (أي ستين فردًا)، وتم بناء مقياس خاص لقياس مستوى المساندة النفسية بين الزوجين، اشتمل على أربعة أبعاد: المساندة العاطفية، المساندة العملية، المساندة الاجتماعية، والمساندة في مواجهة الضغوط. كشفت النتائج عن تدني واضح في بعض أبعاد المساندة، لا سيما العاطفية ومواجهة الضغوط، مما أبرز ضرورة التدخل من خلال برنامج إرشادي متخصص. بناءً على تلك المعطيات، قامت الباحثتان بتصميم برنامج إرشادي نفسي موجه، تم تطبيقه على عينة تجريبية مكونة من أربعة أزواج تم اختيارهم عشوائيًا من بين ذوي الدرجات الضعيفة في المقياس. امتد البرنامج لمدة شهر ونصف، بمعدل ثلاث حصص أسبوعيًا، وضم مجموعة من الجلسات التفاعلية والأنشطة الإرشادية التي تهدف إلى تحسين التفاهم والتواصل، تقاسم الأدوار الأسرية، تنشيط العلاقات الاجتماعية، وتدريب الأزواج على استراتيجيات فعالة في مواجهة الضغوط المرتبطة بوضعية الإعاقة. وقد أظهرت نتائج القياس البعدي تحسنًا ملحوظًا في جميع أبعاد المساندة النفسية، كما بيّنت الاختبارات الإحصائية وجود فروق دالة إحصائيًا بين نتائج القياس القبلي والبعدي لصالح البعدي، مما يؤكد فاعلية البرنامج. كما دعمت المقابلات والملاحظات الميدانية هذا التحسن، حيث لوحظ تغير إيجابي في سلوك وتفاعل الأزواج. خلصت الباحثتان إلى أن التدخل الإرشادي النفسي، إذا ما تم بناؤه على معطيات واقعية وأسس علمية، قادر على تحسين العلاقة الزوجية بشكل فعّال، خاصة لدى الأسر التي تعاني من ضغوط إضافية مرتبطة بتكفلها بأطفال من ذوي الاحتياجات الخاصة. وعليه، أوصت الدراسة بتعميم مثل هذه البرامج الإرشادية في العيادات النفسية والمراكز التربوية، وأكدت على أهمية دمج الأبعاد النفسية والاجتماعية في التكفل الأسري المتكامل." "Study Summary (English Translation): This study aimed to develop a psychological counseling program designed to enhance the level of support between spouses caring for a child with a disability. The initiative stemmed from field observations conducted by the researchers at the “Israa Al-Kheir Clinic for Mental Health and Speech Therapy,” where numerous cases revealed psychological and social difficulties negatively impacting marital relationships and limiting the couple’s ability to cooperate and support one another under the stress of the child’s condition. To accurately assess the situation, the researchers conducted a pilot study involving a sample of thirty couples (sixty individuals). A specific scale was developed to measure psychological support between spouses, covering four dimensions: emotional support, practical support, social support, and support in facing stress. The results revealed significant deficiencies in some areas, particularly emotional support and coping with stress, highlighting the need for a targeted counseling intervention. Based on these findings, the researchers designed a structured psychological counseling program, which was applied to an experimental sample of four randomly selected couples with low support scores. The program lasted for one and a half months, with three sessions per week, and included interactive sessions and counseling activities aimed at improving communication, sharing family responsibilities, enhancing social interactions, and training couples in effective strategies for dealing with the pressures associated with disability. Post-program measurements showed notable improvements in all support dimensions. Statistical tests revealed significant differences between pre- and post-intervention scores in favor of the post-test results, confirming the effectiveness of the program. Field observations and interviews further supported these outcomes, with positive behavioral and interactional changes observed in the couples. The researchers concluded that psychological counseling interventions, when grounded in real data and scientific principles, can effectively improve marital relationships—especially among couples facing additional stress due to raising a child with special needs. Accordingly, the study recommends the implementation of such programs in psychological clinics and educational centers and stresses the importance of integrating psychological and social support in comprehensive family care."
مذكرة ماستر قسم علم النفس وعلوم التربية تخصص تربية خاصة.
Keywords: البرنامج; مستوى المساندة الزوجين; التكفل; الطفل المعاق; The program; level of support for couples; sponsorship; disabled child